Development and evaluation of a DGT sampler using functionalised cross-linked polyethyleimine for the monitoring of arsenic and selenium in mine impacted wetlands. (March 2021) - Sebutsoe, Xolisiwe; Chimuka, Luke; Tutu, Hlanganani; Cukrowska, Ewa
Abstract: Arsenic and selenium are both carcinogenic and their presence in fresh water has attracted the development of robust and accurate monitoring techniques. A new diffusive gradients in thin-films (DGT) sampler was developed and evaluated for the in situ measurements of arsenic and selenium. The binding layer was made from a mixture of sulphonated and phosphonated cross-linked polyethylenimine (SCPEI and PCPEI, respectively). The optimum ratio of a SCPEI and PCPEI resin mixture was determined. The DGT sampler was calibrated under laboratory conditions to determine the influence of sample turbulence, concentration and pH. The optimised DGT passive sampler was field deployed in a mine impacted dam for 12 days. Binding layer optimisation shows that the polymers had to be mixed in a specific ratio of 80% sulphonated and 20% phosphonated per 0.8 g of the resin mixture, in the loose polymer form. Embedding the resin mixture in agarose gel reduced the uptake of both arsenic and selenium dramatically. At sample pH 3.0 and 5.0, the DGT sampler did not show significant differences in uptake of the two elements during the 15 day deployment. The passive sampler had limited adsorption capacity and was found better suited for dilute solutions, with concentrations below 0.5 mg L −1 of the target metals. This effect was more pronounced when exposed to dam water which had competing cations. Cations may have reduced the capacity by binding to the PEI backbone via the large number of amine groups. Nonetheless, these cations did not show linear uptake. Highlights: Sulphonated and phosponated cross-linked polyethylenimine used asDGT passive sampler binding layer for arsenic and selenium. Calibration suggests that the DGT passive sampler can operate in stagnant conditions under the pH range of natural water. Use of a polymeric adsorbent as binding layer shows the need for a highly inert polymer backbone. Presence of cations limited adsorption of arsenic and selenium by the passive sampler.